2015
DOI: 10.1016/j.actbio.2015.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Probing carbonate in bone forming minerals on the nanometre scale

Abstract: To devise new strategies to treat bone disease in an ageing society, a more detailed characterisation of the process by which bone mineralises is needed. In vitro studies have suggested that carbonated mineral might be a precursor for deposition of bone apatite. Increased carbonate content in bone may also have significant implications in altering the mechanical properties, for example in diseased bone. However, information about the chemistry and coordination environment of bone mineral, and their spatial dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 85 publications
1
30
0
Order By: Relevance
“…Recent studies have proved that EELS can be successfully used for the investigation of biominerals by providing highly relevant information concerning their formation mechanisms. [16][17][18][19][20] Here, incipient RPs from human kidneys were analyzed using Transmission Electron Microscope (TEM) and STEM imaging combined with spatially-resolved EELS to improve our understanding of the events that precede the pathogenic evolution of RPs. For this purpose, a library of EELS fingerprints for RP investigations was built relying on data gathered from a calculi collection.…”
mentioning
confidence: 99%
“…Recent studies have proved that EELS can be successfully used for the investigation of biominerals by providing highly relevant information concerning their formation mechanisms. [16][17][18][19][20] Here, incipient RPs from human kidneys were analyzed using Transmission Electron Microscope (TEM) and STEM imaging combined with spatially-resolved EELS to improve our understanding of the events that precede the pathogenic evolution of RPs. For this purpose, a library of EELS fingerprints for RP investigations was built relying on data gathered from a calculi collection.…”
mentioning
confidence: 99%
“…Carbon K-edges of non-mineralised and mineralised collagen fibrils (Fig. 4 ) were compared with carbon K-edges of the amorphous carbon film support (AC) and carbonated hydroxyapatite (CHA) 26 .
Figure 4 The carbon K near edge structures of turkey tendon fibrils (collected from 14 week old specimen), carbonated HA (CHA) and amorphous carbon (AC).
…”
Section: Resultsmentioning
confidence: 99%
“…Oxygen spectra of mineralised regions were aligned using peak D, which was set to an energy-loss of 539 eV 26 . The calibration of energy scale of non-mineralised regions was confirmed by observation of the zero loss peak before and after the acquisition.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, since the sub-units are derived from soluble geological minerals, then there is a likelihood the minerals themselves have a known structural class in terms of crystallographic diffraction, thermal gravimetric signature, x-ray, and electron patterns (Yang et al 2013b). Furthermore, previous research has shown the biomineralized scales to exhibit property grading with very little change in composition so the sub-units may also have identifiable packing arrangements, grain shape, grain size distributions, and unique grain orientations at interfaces throughout the hierarchal levels (Chen et al 2011;Allison et al 2013;Yang et al 2013a;Yang et al 2013b (Lee et al 2011;Torres et al 2008;Tai et al 2005;Bruet et al 2008;Yang et al 2013b;Garrano et al 2012;Landis 1995;Ikoma et al 2003;Lin et al 2011;Song et al 2010;Chang and Chen 2013;Liu et al 2008;Cuy et al 2002;Waite and Broomell 2012;Bozec et al 2005;Zhang et al 2008;Klosowski et al 2015;McNally et al 2013;Rho and Pharr 1999;Bertassoni and Swain 2012;and Rodriguez-Florez et al 2013). Furthermore, Table 3.1 provides a systematic means to critically evaluate experimental methods that may be useful in interpreting the structural, chemical, and mechanical processes when descending the hierarchical scales of highly complex heterogeneous composite materials.…”
Section: Questions Developed From Hypothesis (H)mentioning
confidence: 99%